Achilles as an ambivalent hero in Late Antique latin poetry - Dominik, William J. (2023)
An analysis of the role of Achilles in late antique Latin poetry illustrates that he is viewed both as a positive role model and as a negative exemplum or an inferior foil. Both the positive and unfavorable aspects of Achilles’ characterization are linked to the aspirations of the Roman elite and the values emphasized by both pagan and Christian Latin poets.